2012
DOI: 10.21236/ada566281
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics of Condensed Phase Reactions in Sub-Centimeter Geometries

Abstract: In this work, the combustion characteristics of the exothermic systems Ti/C, Ni/Al, 3Ni/Al and combinations thereof, are examined in small diameter aluminum tubes (3-6 mm ID). Tailoring the overall exothermicity of the reactant system is accomplished by varying the reaction combination, stoichiometry, and the addition of alumina as a diluent. For the combined reactive system, Ti/C-3Ni/Al, it is shown that at 40 wt.% Ti/C content, the failure diameter lies between 3 and 4 mm. While at a Ti/C content of 30 wt.%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
6
1
Order By: Relevance
“…Additionally, direct comparison of microchannels with an effective inner diameter of 4.8 mm (with and without Grafoil) also resulted in little difference being observed in the combustion velocity ( Figure 3B). This is in contrast to our previous results for the Ti/C-Ni/Al-Al 2 O 3 system where the overall propagation rate increased along with the range of consolidated densities where full propagation was observed [19]. Therefore, for these compositions the added benefits of reducing the radial heat loss with Grafoil was not significant enough to observe a change in combustion velocity.…”
Section: Effect Of Minimizing Radial Heat Loss With Thermal Barrierscontrasting
confidence: 99%
See 4 more Smart Citations
“…Additionally, direct comparison of microchannels with an effective inner diameter of 4.8 mm (with and without Grafoil) also resulted in little difference being observed in the combustion velocity ( Figure 3B). This is in contrast to our previous results for the Ti/C-Ni/Al-Al 2 O 3 system where the overall propagation rate increased along with the range of consolidated densities where full propagation was observed [19]. Therefore, for these compositions the added benefits of reducing the radial heat loss with Grafoil was not significant enough to observe a change in combustion velocity.…”
Section: Effect Of Minimizing Radial Heat Loss With Thermal Barrierscontrasting
confidence: 99%
“…At low densities, the reacting compact may not transfer enough energy to react subsequent layers, while at high densities the increased thermal conductivity of the compact may conduct heat away from the reaction zone too quickly resulting in self-quenching of the reaction. Initial screening of the Ti/C-3Ni/Al system in 4.8 mm Al microchannels found that the reaction was self-sustaining only at compositions containing in excess of 35 wt.-% Ti/C [19]. This result is specific to the powders used in this study since the overall reactivity is dependent on the particle size, morphology, and intimacy of the reactants.…”
Section: Effect Of Consolidated Density On Combustion Wave Velocitymentioning
confidence: 76%
See 3 more Smart Citations